2022
DOI: 10.1007/s00330-022-09187-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the radiomics quality score applications: an EuSoMII Radiomics Auditing Group Initiative

Abstract: Objective The main aim of the present systematic review was a comprehensive overview of the Radiomics Quality Score (RQS)–based systematic reviews to highlight common issues and challenges of radiomics research application and evaluate the relationship between RQS and review features. Methods The literature search was performed on multiple medical literature archives according to PRISMA guidelines for systematic reviews that reported radiomic quality asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 72 publications
3
33
0
Order By: Relevance
“…The mean RQS was 11.34 ± 3.68, resulting in 31.27 ± 10.40%. This result is higher than the average results, with an RQS score of 18.87% reported in a systematic review of RQS applications published by the EuSoMII Radiomics Auditing Group [ 39 ]. This difference may be largely explained by the limits of the RQS tool itself.…”
Section: Discussionmentioning
confidence: 56%
“…The mean RQS was 11.34 ± 3.68, resulting in 31.27 ± 10.40%. This result is higher than the average results, with an RQS score of 18.87% reported in a systematic review of RQS applications published by the EuSoMII Radiomics Auditing Group [ 39 ]. This difference may be largely explained by the limits of the RQS tool itself.…”
Section: Discussionmentioning
confidence: 56%
“…Sollini et al [ 16 ] declared that the number of oncological image minding studies was six-times of those in non-oncological field. Spadarella et al [ 17 ] found that more than nine tenths of their included systematic reviews focused on oncological radiomics. It is not surprising because the concept of radiomics was raised to mine the medical images for extra deeper information related to oncological genomics [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although an increasing number of systematic reviews and meta-analyses are published in various medical fields, including radiomics [ 15 ], it is still unclear how far radiomics is from current research to clinical application [ 9 13 ]. There were systematic reviews attempt to cover a wide range of topics in radiomics [ 16 , 17 ]. However, the number of published primary radiomics studies was too large to summarize in one single systematic review [ 16 ], and the evidence level rating of current radiomics was out of the aim of a methodological systematic review [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 100 However, the exponential growth in the number of publications and commercial products has not been matched by an equal increase in the quality or transparency of study methodology. 101 , 102 This is supported by a recent survey of all systematic review papers using the Radiomics Quality Score to assess methodological quality and transparency in medical imaging. Of the 44 included articles, each evaluating an average of 32 research papers, the median score was 21%, with a stable trend over the years (ranging from 2018 to 2021).…”
Section: Must Have Qualitiesmentioning
confidence: 91%